Plan de branding para determinar el posicionamiento de la marca de la industria de alimentos Cordovez “Quecor” CIA. LTDA. en la parroquia de Alóag provincia de Pichincha en el periodo 2015 - 2016 - Cueva Pila, Angélica Gabriela (2016)
The objetive of the work is to develop a “Branding's Plan to determine the positioning of the brand of the Food industry Cordovez "QUECOR"”, which claims that the products are recognized and could be commercialized to local and national level, benefiting the profitability of the organization. There were identified the fundamental categories that involve the variables of the investigation for the sustenance of the theoretical frame, it developed the situational internal analysis the strengths and weaknesses and in the external environment the opportunities and damages, equally the strategic tools were design for the positioning of the brand….